Integrasi Islam Dalam Pembelajaran Matematika: Perspektif Calon Guru Matematika Pada Perkuliahan Micro Teaching - Imamuddin M.; Isnaniah Isnaniah; Hayatun Nufus (TA'DIBAN, 2023)
Micro teaching is a compulsory course that must be taken by prospective mathematics teacher students of UIN Bukittinggi. Micro teaching courses train the basic teaching skills of prospective mathematics teachers. One of the lessons that is trained to prospective mathematics teacher students is Islamic integration mathematics learning. The purpose of this study is to describe the perspectives of prospective mathematics teacher students on Islamic integration mathematics teaching that students have practised. This research is a descriptive study with the research subjects are UIN Bukittinggi students who take micro teaching in the sixth semester totalling eleven students. Data were collected using a questionnaire that uses a 1-4 scale. The analysis was carried out using the average formula and then matched against the assessment criteria table. The results of this study are prospective mathematics teacher students have a very good perspective on Islamic integration mathematics learning that has been trained. Islamic integrated mathematics learning is very good in motivating and useful, new learning, interesting, challenging, useful, makes it easier for students to understand mathematical concepts and can add insight to students related to Islamic knowledge.